USE OF WEB-BASED POETIC DEVICE TOOLS AS A LEARNING MEDIA FOR CREATIVE WRITING OF ENGLISH POETRY - Sarif Syamsu Rizal; Sri Oemiati; Haryati Sulistyorini (Universitas Muhammadiyah Makassar, 2023)
This research is entitled